PELATIHAN GURU YANG HEBAT, INOVATIF, KREATIF, DAN MENYENANGKAN: Upaya Memperkuat Kompetensi Profesional Guru di Desa Cihanjawar - Yulianty S, Nadya; Hilaluddin, Agus (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
A teacher is a personal figure who is a role model and role model for his students, because every word, action and behavior will become a highlight for his students. Teachers are also learning agents (learning agents) who act as facilitators, boosters, motivators, inspirers and learning engineers for students. An ideal teacher needs to have broad insight and knowledge both regarding their students and their learning strategies. Great Teacher, Innovative, Creative and Fun Training is training that provides insight and also soft skills to Teachers so that through this training they are able to increase Teachers' knowledge to become innovative, creative and fun Teachers, and improve Teachers' skills and professionalism in carrying out learning to students. This method of implementing Great, Innovative, Creative and Fun Teacher Training was carried out in Cihanjawar Village, Bojong District, Purwakarta Regency, given to 30 teachers from Cihanjawar Village which were packaged in the form of seminars and training conducted indoors. The results of the training showed that there was an increase in knowledge regarding teachers' professional abilities in implementing learning for students by 80%. Meanwhile, the practice of soft skills to become an innovative, creative and innovative teacher increased by 85%.